Influence of damping on high-speed VCSEL data transmission - Haglund, Emanuel P. (My University, 2013)
The vertical-cavity surface-emitting laser (VCSEL) is a low-cost light source with properties well suited for short-reach high-speed data transmission. Due to the increasing demand for high-speed data communication capacity, both in data centers and home connections, there is need for low-cost solutions operating at high bit rates, which makes the VCSEL an attractive option in such optical systems. Commercially available VCSELs are, however, limited to bit rates of around 10 Gbit/s, which is far lower than the data rates specified in upcoming standards. This means that the development of higher speed VCSELs is required. This work has studied the influence of damping on high-speed VCSEL data transmission performance, through an investigation of the large signal properties. VCSELs with different damping (obtained by shallow surface etches of different depths) were characterized through static and dynamic measurements, with emphasis on characterizations during large signal data transmission. Through investigations of the timing jitter and the bit error rate (BER), it was found that using a VCSEL with a K-factor of 0.16 ns and a D-factor of 9 GHz/mA^(1/2), provided the best high-speed properties among the tested devices. This particular VCSEL was able to achieve record high data rates, with 57 Gbit/s back-to-back (BTB), and 55 Gbit/s and 43 Gbit/s over 50 m and 100 m of OM4-fiber, respectively.
Keywords: Fotonik; Informations- och kommunikationsteknik; Photonics; Information & Communication Technology